Hamstring and knee injuries are associated with isometric hip and trunk muscle strength in elite Australian Rules and Rugby League players - Hajek, M.; Williams, M. D.; Bourne, M. N.; Roberts, L. A.; Morris, N. R.; Shield, A. J.; Headrick, J.; Duhig, S. J. (Journal of Science and Medicine in Sport, 2023)
Objectives This study investigated relationships between isometric trunk and hip extensor strength, lumbar muscle morphology, and the risk of hamstring and knee ligament injuries in Australian Football League and National Rugby League players.